Preferensi Habitat Ikan Gabus [Channa striata (Bloch 1793)] di Perairan Rawa Aopa, Sulawesi Tenggara - Muliani Muliani; Muhammad Ramli; Asriyana Asriyana (Jurnal Ilmu Pertanian Indonesia, 2021)
The use of habitat by fish is closely related to efforts to find the best conditions for the survival of these fish. This study aims to analyze the habitat preferences of Striped snakehead in Rawa Aopa waters, Southeast Sulawesi. This research was conducted from November 2018 to February 2019 in the waters of Swamp Aopa Southeast Sulawesi. Fish collection using traps. The constancy and fidelity index determined the preference of striped snakehead for habitat type. A total of 1024 striped snakehead fish were caught during the study with a length range of 200,0-420,0 mm and 69,0-596,0 g weight. Striped snakehead measuring 200-367 mm were consistent in occupying habitats with a slightly dense to dense water plant density, while sizes 368-388 and 389-430 mm were consistent in habitats with sparse water plant density. The preference level of striped snakehead fish size 389-430 mm to habitats with rare aquatic plants is very high (Fij = 6). Therefore, the size can be used as an indicator of habitats with the rare aquatic plant category. The preference for 200-367 mm striped snakehead fish in dense aquatic plant habitats indicates that these habitats are foraging, growing, and protective zones. Keywords: Channa striata, fish habitat, Rawa Aopa, Southeast Sulawesi, stripe snakehead